2018
DOI: 10.18632/oncotarget.24275
|View full text |Cite
|
Sign up to set email alerts
|

The c-Raf modulator RRD-251 enhances nuclear c-Raf/GSK-3/VDR axis signaling and augments 1,25-dihydroxyvitamin D3-induced differentiation of HL-60 myeloblastic leukemia cells

Abstract: Differentiation therapy is used in cancer treatment. Epidemiologic studies showed that higher vitamin D levels are associated with reduced cancer risks. However, the therapeutic doses needed for differentiation are accompanied by hypercalcemia and intolerable pathological sequelae. In the present work we evaluated if RRD-251, a small-molecule, can enhance vitamin D3-induced differentiation of leukemic cells, in the hope of decreasing the needed vitamin D3-dose.We demonstrate that RRD-251 enhances vitamin D3-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…We analyzed the expression of total RB and pS608-RB status in these cells. Consistent with other reports [14, 16,39,[45][46][47], ATRA promoted the down-regulation of total RB and diminished the amount of pS608-RB, and co-treatment with roscovitine enhanced this ( Figure 6F and 6G). Thus, roscovitine enhanced ATRA-induced effects on G1/G0 cell cycle arrest through regulatory proteins of the p27/cyclin E1/ Cdk2/RB pathway.…”
Section: Roscovitine Enhances Atra-induced Changes In Certain Canonicsupporting
confidence: 93%
See 1 more Smart Citation
“…We analyzed the expression of total RB and pS608-RB status in these cells. Consistent with other reports [14, 16,39,[45][46][47], ATRA promoted the down-regulation of total RB and diminished the amount of pS608-RB, and co-treatment with roscovitine enhanced this ( Figure 6F and 6G). Thus, roscovitine enhanced ATRA-induced effects on G1/G0 cell cycle arrest through regulatory proteins of the p27/cyclin E1/ Cdk2/RB pathway.…”
Section: Roscovitine Enhances Atra-induced Changes In Certain Canonicsupporting
confidence: 93%
“…ATRA induces these cells to undergo myeloid differentiation and G0 cell cycle arrest that depends on a sustained MAPK pathway signal with up-regulation and unanticipated translocation of c-Raf to the nucleus [14,15]. In the nucleus, c-Raf interacts with the RB tumor suppressor protein [14,16,17]. RB is considered a master regulator of the cell cycle that becomes progressively phosphorylated with G1/S/G2 progression.…”
Section: Research Papermentioning
confidence: 99%
“…Therefore, it is possible that vitamin D may improve survival time in patients with undifferentiated, but not differentiated carcinoma. In-vitro experiments [2,3,4] have shown the potential for vitamin D to induce differentiation of undifferentiated cancer cells in vivo. In fact, a clinical pilot trial indicated that vitamin D may increase differentiation in the normal colorectal mucosa of patients with colorectal adenoma [22], although that trial did not include patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The 25(OH)D is further activated in the kidneys by 1-alpha-hydroxylase to 1,25-dihydroxyvitamin D, which facilitates calcium absorption and plays an important role in bone health. A more recent discovery that most tissues, as well as cancers, have 1-alpha-hydroxylase to convert serum 25(OH)D to 1,25(OH)2D, along with vitamin D receptors, which are steroid hormone nuclear receptors that regulate a variety of genes within a cell [1], has provided new insights into the function of vitamin D. In particular, vitamin D has been demonstrated to induce differentiation of cancer cells in vitro [2,3,4], which leads to the hypothesis that vitamin D supplementation may improve prognosis of patients with poorly differentiated carcinoma in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation